Necesidad de incorporar una tabla porcentual sancionadora que guarde relación con el grado de perjuicio en el delito de mal uso de productos derivados de hidrocarburos, gas licuado de petróleo - Reyes Sarango, Darwin Rolando (2017)
The present research work, whose theme is "THE NEED TO INCORPORATE A PERCENTAGE SANCTIONING TABLE THAT KEEP RELATED TO THE DEGREE OF INJURY IN THE CRIME OF MISUSE OF PRODUCTS DERIVED FROM HYDROCARBONS, PETROLEUM LIQUID GAS", is the objective of this Work of Investigation is oriented to the juridical and critical analysis of the procedures and claims in the application of the sanctions within our Code Integrated Integral Penalty, not to establish a percentage table for the crimes of hydrocarbons according to the amounts thereof. Article 76, paragraph 6, of the Constitution of the Republic of Ecuador, provides that the law will establish the proportionality between infractions and penal sanctions, administrative of another nature, so that the criminal legal system is responsible for the classification Of the different behaviors considered punishable as well as to establish the different procedures for their prosecution, regarding the penalties of the Code of Criminal Integral, establishes a minimum and a maximum of time with regard to the custodial sentence, leaving to Criterion of the judge and other procedural rules to determine the penalty to be imposed. The principle of proportionality established in the Constitution of the Republic of Ecuador is the one that regulates the punitive power of the state against the prosecution of offenses established in criminal law, but logically this must also obey the degree of participation of the active subject of the crime, As well as the circumstances in which the offense occurred and, more importantly, consideration should be given to the degree of harm that the offense causes to victims. Thus, Article 264. On the storage, transportation, packaging, marketing or illegal distribution or misuse of products derived from hydrocarbons, liquefied petroleum gas or biofuels, states that: A person who, without proper authorization, stores, transports, Packaging, marketing or distributing hydrocarbon products or their derivatives, including liquefied petroleum gas and biofuels or being authorized, diverts it to a different segment, shall be punished by imprisonment for one to three years. Individuals using hydrocarbon derivatives, including liquefied petroleum gas and biofuels, in activities other than those expressly permitted by the Law or competent authority, shall be punished by imprisonment for one to three years. The current legislation criminalizes the misuse of liquefied petroleum gas in Article 264, of the Integrated Organic Criminal Code, and establishes a sanction of one to three years, without considering the amount of oil derivatives that would be misused In the offense, which could lead to the misuse of a single cylinder of domestic gas ($ 2.60), which would result in a serious damage of approximately $ 12, oo, would be subject to a custodial sentence of one to Three years without distinction that the same penalty would apply to anyone who misuses this derivative in an indefinite amount, which is illogical to say less and flagrantly violates the constitutional rights of persons prosecuted for this type of infractions. The present thesis of Legal Investigation is structured as follows: First, a Conceptual Framework, which includes concepts and definitions of the Sanctions, conditional suspension, among other concepts that will give greater emphasis to the proposed topic; A Doctrinal Framework, which covers the doctrines of writers and scholars on how they obtain conditional suspension of sentence. Legal Framework, which includes the analysis of the Constitution of the Republic of Ecuador, the Integrated Organic Criminal Code, the Organic Code of Judicial Function and then we have a Comparative Legislation, since it served to make an analysis of the matter of other countries And to extract the most positive. Secondly the research work comprises a field study in which surveys and interviews are developed to those who know the law in which they help me to determine or contrast the objectives and hypotheses raised. In the third place after the analysis of the field research, the conclusions and recommendations were made and finally a legal proposal necessary to solve the problem.